2016
DOI: 10.1111/acer.13064
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Safety and Initial Efficacy of Ivermectin for the Treatment of Alcohol Use Disorder

Abstract: Background Ivermectin (IVM) is an antiparasitic agent that has been shown to reduce alcohol intake in mice, suggesting IVM as a potential treatment for alcohol use disorder (AUD). However, the safety profile of IVM administered in combination with an intoxicating dose of alcohol has not been characterized in humans. Methods This pilot project sought to provide the first clinical evidence that IVM could be repositioned as an AUD pharmacotherapy by examining 1) the safety of combining IVM (30 mg oral QD) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Of note, the safety and initial efficacy of co-administration of a single 30-mg dose of ivermectin and intravenous alcohol infusion in alcoholic patients was recently tested. In this study, ivermectin (30 mg) was found to be safe and well tolerated where the number and severity of reported adverse effects were low and did not differ from the placebo session (Roche et al, 2016). Although ivermectin did not differ from placebo in regards to reducing alcohol cue-induced craving or basal alcohol craving, the study represented an important first step in developing this class of molecules as pharmacotherapies for AUD.…”
Section: Discussionmentioning
confidence: 71%
“…Of note, the safety and initial efficacy of co-administration of a single 30-mg dose of ivermectin and intravenous alcohol infusion in alcoholic patients was recently tested. In this study, ivermectin (30 mg) was found to be safe and well tolerated where the number and severity of reported adverse effects were low and did not differ from the placebo session (Roche et al, 2016). Although ivermectin did not differ from placebo in regards to reducing alcohol cue-induced craving or basal alcohol craving, the study represented an important first step in developing this class of molecules as pharmacotherapies for AUD.…”
Section: Discussionmentioning
confidence: 71%
“…The reported sample draws from baseline data collected as a part of four human laboratory studies. Three studies examined pharmacotherapies for alcohol use: naltrexone in an Asian American sample (n = 199; (Ray et al, 2018), ibudilast (n = 138; (Ray et al, 2017), and ivermectin (n = 74; (Roche et al, 2016b). The fourth study was an alcohol self-administration study (n = 140; (Bujarski et al, 2018), resulting in a total sample of 551 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Non-treatment seeking, heavy alcohol users (N = 338) were recruited from the greater Los Angeles community for participation in three human laboratory studies of AUD conducted at the University of California Los Angeles (UCLA). Two studies tested novel pharmacological interventions for AUD, specifically ibudilast (Ray et al, 2017a) and ivermectin (Roche et al, 2016) and a third study tested the relationship between subjective responses to alcohol and progressive ratio alcohol self-administration (Bujarski et al, 2018). All studies were approved by the UCLA Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%